Pertumbuhan dan Hasil Tanaman Selada pada Tiga Jenis Tanah Mineral dengan Pemberian Dosis Pupuk Kandang Sapi yang Berbeda - Putra, Dian Pramana; Handajaningsih, Merakati; Riwandi, Riwandi; Fahrurrozi, Fahrurrozi (Akta Agrosia, 2016)
Growing lettuce on lowland mineral soil is an alternative to increase lettuce production. Mineral soil with less fertile soil property needs additional organic matter when it is used as growing medium for lettuce plants . The purpose of this study was to evaluate the growth and yield of lettuce on some mineral soil types and different doses of cow manure. The research was conducted in Surabaya village, Sungai Serut District, Bengkulu City. The experiment used a completely randomized design, two factors, five replications. The first factor was the three types of mineral soils, consisted of Inceptisol, Ultisol and Entisol. The second factor was dose of cow manure, consisted of 0 ton/ha, 5 ton/ha (7.065 g/polybag), 10 ton/ ha (14.13g/polybag), and 15 ton/ha (21.19 g/polybag ). Each combination was repeated 5 times in order to obtain 60 experimental units. The results showed that the mineral Ultisol generally resulted in better growth of lettuce plants than it was at Inceptisol and Entisols, which were indicated by the higher degree of the leaf greenness leaves, root fresh weight and shoot fresh weight. Dosage of fertilizer up to 15 tonnes/ha significantly increased shoot fresh weight and root fresh weight of plants. The interaction between soil types and doses of cow manure occured only on the variable of root fresh weight when it was grown on Ultisol with dose of cow manure at 8.07 tonnes/ha.